Mitophagy in the aging nervous system - Rappe, Anna; McWilliams, Thomas G. (Frontiers in Cell and Developmental Biology, 2022)
Aging is characterised by the progressive accumulation of cellular dysfunction, stress, and inflammation. A large body of evidence implicates mitochondrial dysfunction as a cause or consequence of age-related diseases including metabolic disorders, neuropathies, various forms of cancer and neurodegenerative diseases. Because neurons have high metabolic demands and cannot divide, they are especially vulnerable to mitochondrial dysfunction which promotes cell dysfunction and cytotoxicity. Mitophagy neutralises mitochondrial dysfunction, providing an adaptive quality control strategy that sustains metabolic homeostasis. Mitophagy has been extensively studied as an inducible stress response in cultured cells and short-lived model organisms. In contrast, our understanding of physiological mitophagy in mammalian aging remains extremely limited, particularly in the nervous system. The recent profiling of mitophagy reporter mice has revealed variegated vistas of steady-state mitochondrial destruction across different tissues. The discovery of patients with congenital autophagy deficiency provokes further intrigue into the mechanisms that underpin neural integrity. These dimensions have considerable implications for targeting mitophagy and other degradative pathways in age-related neurological disease.